If S=P(1+rt), make t the subject formula.

1. t= S/r - P/r

2. t= P/Sr - 1/r

3. t= S/r - P/r - 1/r

4. t= S/Pr - 1/r

Guest Sep 14, 2017

#1**0 **

Solve for t:

S = P (r t + 1)

Reverse the equality in S = P (r t + 1) in order to isolate t to the left-hand side.

S = P (r t + 1) is equivalent to P (r t + 1) = S:

P (r t + 1) = S

Divide both sides by a constant to simplify the equation.

Divide both sides by P:

r t + 1 = S/P

Isolate terms with t to the left-hand side.

Subtract 1 from both sides:

r t = (S - P)/P

Solve for t.

Divide both sides by r:

**t = (S - P)/(P r)**

Guest Sep 14, 2017